PENGARUH KARAKTERISTIK INDIVIDU, BUDAYA ORGANISASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (STUDI PADA KARYAWAN INSTALASI RAWAT JALAN RSUD DR. SAIFUL ANWAR MALANG) - Susanti, Susi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
This study aimed to examine the effect of the relationship of individual characteristics, organizational culture, and organizational commitment to employee performance and motivation as a moderating variable in the study of plant employees outpatient Hospital Dr. Saiful Anwar Malang. Poor This research is explanatory. Samples in this study used a sample of 113 respondents 84 employees who work on installation of outpatient Hospital Dr. Results of analysis Partial Least Square (PLS) This study shows that the individual character relationships, organizational culture, different organizational commitment remains significant positive effect on employee performance, motivation to strengthen the relationship between individual characteristics, organizational culture, and organizational commitment to employee performance.Keywords: individual characteristics, organizational culture, organizational commitment, motivation, employee performance.